STUDI ETNOBOTANI TUMBUHAN OBAT PADA MASYARAKAT KAILI RAI DI DESA WOMBO KECAMATAN TANANTOVEA KABUPATEN DONGGALA SULAWESI TENGAH - Zubair Zubair; Samsurizal M. Suleman; Ramadanil Ramadanil (Biology Department, Mathematics and natural science, Tadulako University, 2019)
A research entitled “Ethnobotanical Studies of Medicinal Plant of the Kaili Rai ethnic group in Wombo Village, District Tanantovea, Donggala Regency, Central Sulawesi” has been carried out from December 2016 to February 2017. The research objective was to obtain the information of medicinal plant diversity and its part that utilized and how did their processed as traditional medicine. The research was done by two methods that is using semi structure interview technique to 44 respondents with quisioner sheet and direct interview to village Shaman. The result showed that there were 55 plants species that used by the Kaili Rai ethnic group in wombo village. The highest percentase that used in the part of plants were 60% of leaves.